QoS vs. energy: A traffic-aware topology management scheme for green heterogeneous networks - Yigitel, M. Aykut; Durmaz Incel, Ozlem; Ersoy, Cem (Computer networks (Amsterdam, Netherlands : 1999), 2015)
Increasing environmental awareness combined with the high energy prices has driven the network operators to reduce their carbon dioxide footprint by adopting energy efficient green methods. In this paper, we aim to save energy by both switching base stations on/off and adaptively adjusting their transmission power according to the present traffic conditions for heterogenous wireless cellular networks. We formulate a novel linear programming model for the Traffic-Aware Topology Management (TAM) problem to find the best possible topology which minimizes the overall power consumption of the network while satisfying a certain Quality of Service level in Wideband Code Division Multiple Access packet-switched cellular networks. Although the optimization tools provide the optimum solutions, it is not possible to handle large instances due to the space and computational complexity. Hence, we propose a Green TAM Algorithm to solve the large-scale realistic instances of the formulated problem and compare our results with the results of two previously proposed methods, a greedy heuristic and a commercial optimization tool. We show that the proposed TAM scheme helps to maintain an energy-aware network and saves significant amount of energy by adjusting the network topology to the current traffic conditions adaptively.